Infant and Young Child Feeding practices and risk factors of SAM among beneficiaries of Nutrition Rehabilitation Centre – a cohort study - Chauhan, Dhwani; Chauhan, Naresh T; Patni, Mohamed Anas Mohamed Faruk; Tollawala, Pinakini; Kosambiya, J K (Indian Journal of Community Health, 2024)
Introduction: Mission Balam Sukham's Nutrition Rehabilitation Centre (NRC) combats malnutrition through prevention, treatment, and community engagement, ensuring children receive adequate nutrition for healthy growth. Objective: To document IYCF practices and risk factors of severe acute malnutrition (SAM) among NRC beneficiaries Methodology: A prospective cohort study was conducted comprising of 63 children aged 6 months to 5 years having SAM alongwith complications admitted at NRC of South Gujarat over the duration of 10 months. Observations: 90.5% poverty, 57.1% migrants, 7.9% single parent. 69.8% initiated breastmilk within 1hr, 15.9% weren’t fed with colostrum, 6.3% were given pre-lacteals. 93.7% were exclusively breastfed, 6.3% initiated breastmilk at the time of 6 months. 16%, 60% and 9.8% met the criteria of MDD, MMF and MAD respectively. Boys show significant association on admission and discharge both (t = 2.43, p= 0.026 on admission and t= 2.66, p= 0.015 on discharge). In 13-24 months, MDD group (t = 2.34, p=0.02), children not suffering from anaemia shows significant weight (t=-2.540, p=0.18). Conclusion & Recommendations: Children's weight improvement is linked to better IYCF practices, emphasizing its importance of caregiver attention and education, highlighting need to address cultural barriers and promote practices like exclusive breastfeeding and continuous breastfeeding, focusing on empowering mothers and caretakers.